Error Analysis In Oral Production Made By Student Of Civil Engineering A Case Study: In English Tutorial Program (Etp) At Muhammadiyah University Of Surakarta - PUTRI, AULIA FIRDAUSIA, Prof. Dr. Endang Fauziati, M. Hum (2016)
This research paper is aimed to classify the type of errors, analyze the frequency and dominant, and explain the sources of error. The type of this research is descriptive research. The research collects English Tutorial Program record as the source of the data. The research uses documentation method to select the data. There are 305 data containing of errors. The researcher use Clark and Clark theory and Dulay Burt, and Krashen theory to analyze the error. They are speech error, morphological error and syntactical error. In speech errors are filled pause (81, 96%), Repeat (44, 27%), Silent Pause (19, 67%), Stutters (6, 22%), Injection (1, 96%), correction (0, 65%), Slip of the Tongue (0, 98%). Morphological error are vocabulary error (1, 96%), Pronunciation (9, 83%), Omission of Bound (1, 63%). Syntactical error are omission of Modal (will) (1, 31%), omission of preposition (1, 31%), Question Construction (1, 31%) and the last Wrong in Word Selection (0, 65%). Key Words : error analysis, oral production.